2011
DOI: 10.1161/circulationaha.111.021675
|View full text |Cite
|
Sign up to set email alerts
|

m-Calpain Induction in Vascular Endothelial Cells on Human and Mouse Atheromas and Its Roles in VE-Cadherin Disorganization and Atherosclerosis

Abstract: Background-Although dysfunction of VE-cadherin-mediated adherence junctions in vascular endothelial cells (ECs) is thought to be one of the initial steps of atherosclerosis, little is known regarding how VE-cadherin is disrupted during atherogenic development. This study focused on the role of calpain, an intracellular cysteine protease, in the proteolytic disorganization of VE-cadherin and subsequent progression of atherosclerosis. Methods and Results-Increased expression of m-calpain was observed in aortic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 38 publications
3
106
1
Order By: Relevance
“…In contrast, Takano et al recently revealed that conditional knockout mice, in which m-calpain is expressed in the placenta but not in the fetus, survive to adulthood 26) . Thus, m-calpain is unlikely to play an essential role in cardiovascular development in the fetus, but rather plays critical roles in placental integrity, since abnormalities in placental development have been shown to cause cardiovascular tension 4) and atherosclerotic vascular disease 7) . The biological implications of the differential roles of calpains under physiological and pro-atherogenic conditions remain unknown; however, we hypothesized that pathogenic mediators [e.g., modified low-density lipoprotein (LDL) in atherosclerosis, angiotensin Ⅱ in hypertension] lead calpains to an over-active state or otherwise abnormal elevation of expression, thereby accelerating pro-atherogenic conditions.…”
Section: Molecular Characteristics Of Calpainsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Takano et al recently revealed that conditional knockout mice, in which m-calpain is expressed in the placenta but not in the fetus, survive to adulthood 26) . Thus, m-calpain is unlikely to play an essential role in cardiovascular development in the fetus, but rather plays critical roles in placental integrity, since abnormalities in placental development have been shown to cause cardiovascular tension 4) and atherosclerotic vascular disease 7) . The biological implications of the differential roles of calpains under physiological and pro-atherogenic conditions remain unknown; however, we hypothesized that pathogenic mediators [e.g., modified low-density lipoprotein (LDL) in atherosclerosis, angiotensin Ⅱ in hypertension] lead calpains to an over-active state or otherwise abnormal elevation of expression, thereby accelerating pro-atherogenic conditions.…”
Section: Molecular Characteristics Of Calpainsmentioning
confidence: 99%
“…Interestingly, calpains are capable of promoting NF-κB signals via the degradation of IκBα without affecting phosphorylation of this inhibitor 33,34) . Since m-calpain is induced in ECs in atherosclerotic lesions 7) , it is not surprising that NF-κB signals are promoted in ECs during atherogenesis through calpain-induced degradation of IκBα. This hypothesis is consistent with our previous data: the expression levels of NF-κB as well as those of adhesion molecules or cytokines in the pro-atherogenic aorta in ldlr −/− mice decreased significantly following administration of the calpain inhibitors, calpeptin and calpain inhibitor Ⅱ .…”
Section: Pro-atherogenic Roles Of Calpainsmentioning
confidence: 99%
See 3 more Smart Citations